2018
DOI: 10.1038/s41433-018-0029-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of photodynamic therapy and navigated microsecond laser for chronic central serous chorioretinopathy

Abstract: nMSL seems to be superior over PDT in improving visual and anatomical outcomes at 6 months and can be considered as a cheap alternative to PDT in treatment of CSCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 36 publications
(48 reference statements)
0
16
0
4
Order By: Relevance
“…Ntomoka et al [60] showed that SML is superior in terms of efficacy to PDT (visual acuity improvement 0.12 vs. −0.02 (p = 0.039), SRF resolution 59% vs. 21.7%, CMT reduction 85.5 μm vs. 24.47 μm (p = 0.02), respectively, 6 months after treatment). Nevertheless, these outcomes have not been confirmed by PLACE trial results recently published by van Dijk et al [61]; in particular, a higher rate of SRF resolution after half-dose PDT treatment compared to SML treatment has been shown, both at the first post-treatment evaluation at 6-8 weeks (51.2% vs. 13.8%, p < 0.001) and after 8 months (67.2% vs. 28.8%, p < 0.001), despite the improvement in vision-related quality of life being similar for both treatments.…”
Section: Laser Treatmentsmentioning
confidence: 99%
“…Ntomoka et al [60] showed that SML is superior in terms of efficacy to PDT (visual acuity improvement 0.12 vs. −0.02 (p = 0.039), SRF resolution 59% vs. 21.7%, CMT reduction 85.5 μm vs. 24.47 μm (p = 0.02), respectively, 6 months after treatment). Nevertheless, these outcomes have not been confirmed by PLACE trial results recently published by van Dijk et al [61]; in particular, a higher rate of SRF resolution after half-dose PDT treatment compared to SML treatment has been shown, both at the first post-treatment evaluation at 6-8 weeks (51.2% vs. 13.8%, p < 0.001) and after 8 months (67.2% vs. 28.8%, p < 0.001), despite the improvement in vision-related quality of life being similar for both treatments.…”
Section: Laser Treatmentsmentioning
confidence: 99%
“…Nevertheless, baseline CMT was better than other studies (290.5 µm vs 402 µm vs 326.5 µm vs 369 µm) which can explain the lower decrease in CMT. 7,12,14 Ntomoka et al 7 was the only study that evaluated macular layers besides CMT. In our study, SRF was also less severe than in other studies (26.5 µm vs 160.5 µm).…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Other available treatment options include mineralocorticoid antagonist (ie spironolactone and eplerenone), focal laser or anti-vascular endothelial growth factor (VEGF) therapy. [7][8][9] There is overall poor evidence for the use of systemic and intravitreal medications; mineralocorticoid receptor antagonists may have the greatest potential from this class of treatments. Conventional thermal photocoagulation may be used in selected cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a recent study compared PDT with navigated subthreshold laser in an albeit smaller study (45 eyes of 39 subjects). [ 59 ] Navigated laser was applied as confluent spots at areas of focal leakage identified on earliest phase of fluorescein angiography. Navigated laser appeared to be superior to PDT in improving both anatomic and visual function at 6 months.…”
Section: Considerations In Treatment Of Cscmentioning
confidence: 99%